APPLICATION OF DESIGN THINKING AND PROTOTYPE METHODS IN THE DESIGN OF MOBILE-BASED HIJAB E-COMMERCE APPLICATIONS:CV REN - Rizaldi Putra; Ade Oki Pebiansyah; Lambok Rommy Sulaeman; Nurali Nurali; Deni Utama (SEAN Institute, 2023)
CV REN is a company engaged in convection. CV REN is one part of PT Minori , a Job Training Institute (LPK) that sends trainees to Japan. CV REN is currently still producing and selling using conventional techniques, namely manually. In addition, at this time Muslim trainees who wear hijab who will go to Japan are not allowed to use hijab that uses needles or similar tools because it is considered to be dangerous for both the trainees themselves and consumers. Therefore, a special hijab e-commerce application was designed that does not use needles, for trainees who want to buy hijab so that it can be used while interning in Japan, easily, quickly trusted. Observations, interviews and literature studies were conducted for data collection. The design thinking method is also used in the analysis stage of application design needs.